2021
DOI: 10.1155/2021/9932218
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Resveratrol on Aging and Age‐Related Diseases

Abstract: The aging of population has become an issue of great concern because of its rapid increase. Aging is an important risk factor of many chronic diseases. Resveratrol could be found in many foods, such as grapes, red wine, peanuts, and blueberries. Many studies reported that resveratrol possessed various bioactivities, such as antioxidant, anti-inflammatory, cardiovascular protection, anticancer, antidiabetes mellitus, antiobesity, neuroprotection, and antiaging effects. The antiaging mechanisms of resveratrol we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(94 citation statements)
references
References 118 publications
(132 reference statements)
1
71
0
2
Order By: Relevance
“…Studies have shown that resveratrol has beneficial effects on longevity in Drosophila melanogaster [ 160 ], Caenorhabditis elegans [ 160 ], Saccharomyces cerevisiae [ 161 ], Nothobranchius furzeri [ 162 ], and Honey bees [ 163 ]. Many studies have also been performed on mice, rats, and human cells [ 164 ].…”
Section: Drugs With Antiaging Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that resveratrol has beneficial effects on longevity in Drosophila melanogaster [ 160 ], Caenorhabditis elegans [ 160 ], Saccharomyces cerevisiae [ 161 ], Nothobranchius furzeri [ 162 ], and Honey bees [ 163 ]. Many studies have also been performed on mice, rats, and human cells [ 164 ].…”
Section: Drugs With Antiaging Propertiesmentioning
confidence: 99%
“…Disorders such as memory loss or cognitive impairments that occur following aging can be due to oxidative stress, inflammation, and apoptosis in neurons as well as dysregulation in autophagy [ 167 , 166 ]. The antiaging effect of resveratrol in neurodegenerative diseases is due to its neuroprotective effects and by means of reducing inflammation and oxidative stress in neurons, as well as increasing neurogenesis and secretion of neurotransmitters [ 164 ].…”
Section: Drugs With Antiaging Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the accumulation and oxidation of fatty acids in the liver, the antioxidants are consumed and excessive reactive oxygen species are produced, gradually destroying the structure and function of hepatocytes and eventually accelerating the process of NAFLD (33,34). MDA is a representative product of lipid peroxidation (35). This study found that HFD led to an escalating trend of MDA level in mice, while some green teas, namely, Jieyang Chaoqing Tea (GT2) and Fenggang Zinc-Selenium-Enriched Tea (GT3), could significantly lower the MDA level, hence inhibiting the lipid peroxidation and oxidative stress.…”
Section: Effects Of Green Teas On Hepatic Oxidative Stressmentioning
confidence: 99%
“…Resveratrol (trans-3, 5, 40-trihydroxytilbene; RV ) is a naturally polyphenol compound found in berries, nuts, skins of grapes and thus in red wine ( Jang et al., 1997 ). RV has antioxidant, antitumor, antiviral, and free radical scavenging properties, that is thought to be an effective compound for the prevention aging and age-related diseases ( Li et al., 2018 ; Nunes et al., 2018 ; Zhou et al., 2021 , Wang et al., 2021 ). Also, RV is associated with protection against oxidative stress of ovary to increase follicle numbers and prolong the ovary life-extending effect in human and rat model ( Liu et al., 2013 ; Li and Liu, 2018 ; Ochiai and Kuroda, 2019 ).…”
Section: Introductionmentioning
confidence: 99%